THE EFFECTIVENESS OF AUDIT IMPLEMENTATION DURING THE COVID-19 PANDEMIC - Aen Fariah (Green Publisher, 2022)
Implementation of an audit is mandatory for every company that has gone public in particular. Where if the audit process is not carried out it will affect the credibility of the company itself, so that even in a pandemic this must be done. The purpose of this research is to find out the effectiveness of audit implementation during the covid-19 pandemic. The method used is by using qualitative research that is library research, so that the results obtained are obtained from reliable sources such as scientific journals, books and others. The results obtained that the existence of a pandemic makes auditors have to use information technology and IT in carrying out audits. However, with this pandemic phenomenon, it can still affect auditor performance, one of which is the phenomenon of financial reporting delays (audit delay).